2013
DOI: 10.1590/s2317-15372013000400016
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rice seeds treated with zinc, boron, and molybdenum

Abstract: -The objective of this study was to assess physiological quality of seeds and the initial growth of lowland rice seedlings, cv. PUITA INTA-CL, treated with a product based on Zinc, Boron and Molybdenum. The following dosages of product were used: 0 (control), 50, 100, 150 and 200 mL.100 kg -1 seed. A completely randomized experimental design was used, with 10 treatments and four replications. Physiological quality of seeds was assessed by following tests: germination; first count of germination; and length and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Results that corroborate the observed in this work were found by several authors for the SL and RL, but with other species, is seed coating with Zn and B combined or in the use of these isolated way (Ohse et al, 2000;Funguetto, 2007;Masuthi et al, 2009;Tavares et al, 2013a;Tavares et al, 2013). However, Ohse et al (2000) achieved better results for zinc applied separately and negative for the shoot, root and whole plant length of rice when the seeds were given in B + Zn coating together.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Results that corroborate the observed in this work were found by several authors for the SL and RL, but with other species, is seed coating with Zn and B combined or in the use of these isolated way (Ohse et al, 2000;Funguetto, 2007;Masuthi et al, 2009;Tavares et al, 2013a;Tavares et al, 2013). However, Ohse et al (2000) achieved better results for zinc applied separately and negative for the shoot, root and whole plant length of rice when the seeds were given in B + Zn coating together.…”
Section: Resultssupporting
confidence: 92%
“…None of the treatments proved superior to the seed not covered, especially on treatment 6 (addition of 200 g of boric acid and zinc sulfate 150 g.kg -1 of seeds) in which the scored percentage of germination in the first test was equal to zero. Some authors, in contrast, didn't check effect of zinc and boron coating on FGC of rice and wheat seeds (Tavares et al, 2013a;Tavares et al, 2013b 0.73 and 0.03 g.kg -1 of Zn and B for wheat, respectively) used in rice and wheat seeds were much smaller when compared to those employed in this work. Probably the reduction observed in the FGC is associated with osmotic effect provided by micronutrients.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…In relation to the comparison between two cultivars, it is a common approach in experiments that evaluate the performance of seeds subjected to a treatment with nutrients. Several surveys have been conducted in this way, assessing several varieties and their responses to the application of nutrients -such as the works by Tavares et al with barley seeds 43 and rice 44 , the one by Ohse, Cubis 45 with wheat seeds or that by Queiroga, de Queiroz Castro 46 with cotton seeds, to name a fewand significant differences between cultivars were also found, as in the study reported herein.…”
Section: Discussionmentioning
confidence: 70%